2015
DOI: 10.2471/blt.14.140368
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential for improvement of primary care in 34 countries: a cross-sectional survey

Abstract: ObjectiveTo investigate patients’ perceptions of improvement potential in primary care in 34 countries.MethodsWe did a cross-sectional survey of 69 201 patients who had just visited general practitioners at primary-care facilities. Patients rated five features of person-focused primary care – accessibility/availability, continuity, comprehensiveness, patient involvement and doctor–patient communication. One tenth of the patients ranked the importance of each feature on a scale of one to four, and nine tenths o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 16 publications
0
64
0
7
Order By: Relevance
“…It was found that in most of the countries, primary care shows one or more features with a medium or high level of patient-perceived improvement potential. In Poland, “Comprehensiveness” was indicated as a priority area with a medium level of patient-perceived improvement potential [29]. Nevertheless, in comparison to the doctors, Polish patients have explicitly more positive opinions about the quality of primary care.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that in most of the countries, primary care shows one or more features with a medium or high level of patient-perceived improvement potential. In Poland, “Comprehensiveness” was indicated as a priority area with a medium level of patient-perceived improvement potential [29]. Nevertheless, in comparison to the doctors, Polish patients have explicitly more positive opinions about the quality of primary care.…”
Section: Discussionmentioning
confidence: 99%
“…The PHC system in Greece has reported low performance in several areas of quality-based care [4, 16]. A recently published paper of Schäfer et al reported on data from the Quality and Costs of Primary Care in Europe (QUALICOPC), which examined quality indicators as perceived by patients in 34 countries including Greece [17]. Five dimensions of person-focused primary care have been assessed by the QUALICOPC project: accessibility, continuity and coordination, comprehensiveness, patient activation, and doctor–patient communication [1, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Other factors are related to the GP profile [39–41, 43], as well as the characteristics of general practice, such as the practice size [39, 40], personal list system [39, 40] and practice type [44]. The features of the national health system also influence patient satisfaction [45–47]. …”
Section: Introductionmentioning
confidence: 99%